KARAKTERISTIK RESPONSIF LARVA IKAN KEURLING (Tor soro) TERHADAP PAKAN PADA KEHIDUPAN AWAL - Khairul Risky; Azwar Thaib; Nurhayati Nurhayati (Jurnal TILAPIA, 2020)
The keurling fish (Tor soro) is a freshwater fish that has an economical value, with a thick, delicious texture of the flesh. so much popular community. It is indicated by the high demand for the keurling fish meat at a higher price. This research aims to determine how the behavior of the fish larvae in responding to feed supply when the egg yolk starts to thinning and which type of feed is more responded to by the fish larva keurling. The design used in this research is a mixed method design with embedded design with a single container of three treatments, i.e. feeding (artemia), polar red and feed paste. The observed Parameter is the response of a keurling fish larva to feed. The results showed that the feed was very well responded by the fish larva keurling was well-reviewed polar red artemia and the feed paste was not responded at all by the larva of keurling fish.